Plantas medicinales usadas en el vaporeo para curar enfermedades mágicas en el pueblo asháninka - Pachari Pascual, Neri (2025)
This ethnomedical research explains how healers manage the use of medicinal plants to cure magical tropical diseases in the Asháninka family. The study seeks to avoid contracting magical tropical diseases in the young Asháninka population attending the community’s bilingual school. The ethnographic research was conducted with an experienced healer from the Pucharini community and her patient. The methodology includes field visit, interview and biography of the participant and her patient. As a result of this research, the Asháninka population prefers to steam at the healer’s house to heal from themagical tropical disease. However, when they are cured of the disease, they have a medical check-up in a nearby Medical Post, Health Center or Hospital. Finally, most of the Asháninka population is vigilant not to contract magical tropical diseases where they walk, if they contract, they seek a healerto vaporize.